Cleft palate, congenital heart disease, and developmental delay involving MEIS2 heterozygous mutations found in the patient with attention deficit hyperactivity disorder: a case report - Shen, Fang; Li, Junyan; Li, Dandan; Zhou, Hui (Frontiers in Pediatrics, 2024)
This case is the first reported patient with a MEIS2 gene mutation who primarily exhibits pronounced inattention as the main manifestation and is diagnosed with ADHD, requiring methylphenidate treatment. It is characterized by unique clinical features that set it apart from previously reported cases with mutations in the MEIS2 gene. Here, we report a female child with a diagnosis of ADHD and comorbidities. She received treatment with methylphenidate, starting at a dose of 18 milligrams per day, which was gradually increased to 45 milligrams per day based on her attention performance, while also undergoing physical and language rehabilitation training. In addition, the parents involved the child in reading and retelling stories at home every day. After 2 years of treatment, the scale results indicated that the child still had a moderate degree of attention deficit. Therefore, she underwent whole exome sequencing (WES) showing that her MEIS2 gene carries a de novo frameshift mutation (c.934_937del, p. Leu312Argfs*11). After comparing the patient's features with those of other patients who also had the MEIS2 mutation, we discovered that the patient's cleft palate, heart abnormalities, and minor facial dysmorphism were all extremely comparable. A broad forehead, elongated and arched eyebrows, and a tent-shaped upper lip were examples of mild facial dysmorphic traits. Subtypes with phenotypes such as cleft palate, cardiac anomalies, or facial malformations were presented in all previously reported cases of MEIS2 mutations. Furthermore, less common characteristics include ADHD, learning difficulties, hearing loss, recurring respiratory infections, asthma, rhinitis, enuresis, and dental cavities. This case further supports the critical role of genetic testing in patients with ADHD who exhibit a suboptimal response to methylphenidate and present with multiple comorbidities. Furthermore, this case report expands the clinical symptom spectrum associated with MEIS2 gene mutations, providing a broader understanding of the condition.